The Sukka as Temporary or Permanent Dwelling: A Study in the Development of Talmudic Thought - Rubenstein, Jeffrey L. (Hebrew Union College annual, 1993)
The sukka is defined as a dirat ʿarai a 'temporary dwelling' by medieval codes. Yet this concept does not appear in the Mishna, Tosefta, halakhic midrashim, Palestinian Talmud, nor in the first three generations of Babylonian amoraim. This term and its counterpart, dirat qevaʿ 'permanent dwelling', were first introduced by Rava to explain the tannaitic dispute of M. Suk. 1:1. These terms provided Rava with abstract principles with which he could simultaneously interpret that dispute along with three other disputes between the same authorities. Because of their broad scope and abstract nature, Abaye and the stammaim used Rava's concepts to explain other disputes relating to the sukka, then introduced derivative principles, and eventually retrojected these principles to the tannaim themselves. There results a tension between the original tannaitic opinions and the principles imputed to them. The discussion impacts two important issues in critical Talmud study: the development of abstract conceptual categories and the nature of statements attributed to tannaim by later authorities.